2023
DOI: 10.1186/s13054-023-04623-2
|View full text |Cite
|
Sign up to set email alerts
|

Advanced respiratory mechanics assessment in mechanically ventilated obese and non-obese patients with or without acute respiratory distress syndrome

François M. Beloncle,
Jean-Christophe Richard,
Hamid Merdji
et al.

Abstract: Background Respiratory mechanics is a key element to monitor mechanically ventilated patients and guide ventilator settings. Besides the usual basic assessments, some more complex explorations may allow to better characterize patients’ respiratory mechanics and individualize ventilation strategies. These advanced respiratory mechanics assessments including esophageal pressure measurements and complete airway closure detection may be particularly relevant in critically ill obese patients. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…For example, following the standard operating procedure described in Supplementary Table S2, a 10 kg patient will get 60 ml of Vt over 3 s, which gives a flowrate of 1.2 L/min. Airway closure is an increasingly recognized phenomenon in patients with obesity (10), ARDS (up to 40% of adult patients and 65% in those with body mass index of ≥40 kg/m 2 ) (7), and more recently in patients with hydrostatic pulmonary edema caused by cardiogenic shock (11). The prevalence in pediatrics is unknown; however, with the use of this adapted maneuver, it is now possible to study its prevalence in pediatric patients with ARDS or other lung diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, following the standard operating procedure described in Supplementary Table S2, a 10 kg patient will get 60 ml of Vt over 3 s, which gives a flowrate of 1.2 L/min. Airway closure is an increasingly recognized phenomenon in patients with obesity (10), ARDS (up to 40% of adult patients and 65% in those with body mass index of ≥40 kg/m 2 ) (7), and more recently in patients with hydrostatic pulmonary edema caused by cardiogenic shock (11). The prevalence in pediatrics is unknown; however, with the use of this adapted maneuver, it is now possible to study its prevalence in pediatric patients with ARDS or other lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, airway closure is expected to occur more often at a very young age, in patients with obesity and patients with ARDS ( 15 ). Therefore, its routine assessment has been recommended in patients with obesity and ARDS ( 10 ). Several causal factors have been postulated to contribute to airway closure in ARDS, including surfactant impairment, intraluminal fluid accumulation, bronchoconstriction, and the loss of radial traction secondary to elastic fiber destruction, with consequently decreased lung elastic recoil ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…To address these altered mechanics, patients with obesity and ARDS require higher airway pressures to recruit lung units relative to patients with ARDS but normal BMI [19,20 ▪ ]. Studies comparing different PEEP titration strategies in patients with a BMI greater than 35 kg/m 2 , have shown that higher PEEP strategies result in reduced atelectasis, improved lung elastance, and better oxygenation [21].…”
Section: What We Knowmentioning
confidence: 99%
“…For a detailed practical stepby-step approach for bedside measurement of P es and its use in the full context of a lung-protective ventilation strategy, we refer to a recent publication [4 && ]. Theoretically, a P es -guided PEEP setting could prevent atelectasis formation and enhance lung recruitment, which is of particular interest in ARDS and in patients with high P Pl due to other causes, as for example patients with obesity [5]. In this review, we present key concepts and the physiological rationale for titrating PEEP using P es , we discuss the current clinical evidence for this approach, and provide considerations to facilitate bedside implementation.…”
Section: Introductionmentioning
confidence: 99%